Biceps tendon changes and pitching mechanics in youth softball pitchers - Oliver, G. D.; Downs, J. L.; Friesen, K. B.; Saper, M. G.; Anz, A. W.; Andrews, J. R. (International Journal of Sports Medicine, 2021)
With the lack of pitch count regulation, youth softball pitchers are experiencing unremitting high stresses on the anterior shoulder. The purpose of this study was to examine the association of acute changes in the long head of the biceps tendon with pitching kinematics and kinetics in youth softball pitchers following an acute bout of pitching. Twenty-three softball pitchers (12.17±1.50 yrs.; 160.32±9.41 cm; 60.40±15.97 kg) participated. To investigate the association between biceps tendon changes and kinematic and kinetic changes from pre- to post-simulated game, each biceps tendon measure was split into those whose biceps tendon thickness, width, and/or area increased pre- to post-simulated game, and those whose did not. There were significant differences in biceps tendon longitudinal thickness (Z=- 2.739, p=0.006) and pitch speed; as well as a difference between groups in biceps tendon transverse thickness and the amount of change in trunk rotation at the start of the pitching motion (p=0.017) and the amount of change in trunk flexion at ball release (p=0.030). This study illustrates the association of trunk and lower extremity kinematics and shoulder kinetics with morphologic changes in the biceps tendon with an acute bout of windmill softball pitching.